(untitled) (GYMNASIUM, 2017)
The present paper examines promotion and communication issues of CSR activities of major sport clubs and organizations in Greece. CSR can strengthen the image, reputation, achieve financial benefits, and create a competitive advantage for sport teams and organizations. Thus, CSR communications are imperative for their existence, protection of the image and reputation and a safeguard of competitive advantage. The qualitative approach of the present study involves the content analysis of interviews administered to marketing managers in seven different case studies of professional sport clubs and organizations. The query on “How your club or organization promotes or communicates CSR activities?” revealed the promotional mix of CSR activities and illustrated six categories of communication in the Greek professional sport context.